Spatial distribution and sources of nutrients at two coastal developments in South Kohala, Hawai'i. (January 2022) - Panelo, Jazmine; Wiegner, Tracy N.; Colbert, Steven L.; Goldberg, Stuart; Abaya, Leilani M.; Conklin, Eric; Couch, Courtney; Falinski, Kimberly; Gove, Jamison; Watson, Lani; Wiggins, Chad
Abstract: Nutrient sources to coastal waters with coral reefs are not well-characterized. This study documented spatial distributions of nutrients within coastal waters along two developments with coral reefs, and identified nutrient sources through nutrient mixing plots, δ 15 N measurements in macroalgal tissue, and NO3 − stable isotope mixing models. Nutrients decreased from fresh groundwaters to offshore waters, with some surface waters higher in concentrations than benthic ones. Conservative and non-conservative mixing between fresh and ocean waters occurred, the latter suggestive of local nutrient sources and biological removal. δ 15 N in macroalgal tissue and NO3 − concurred that fresh groundwater, ocean water, and fertilizers were dominant nutrient sources. Benthic salinity and NO3 − + NO2 − concentrations illustrated that submarine groundwater discharge delivered nutrients to reefs in pulses ranging from minutes to days. Information generated from this study is imperative for developing management actions to improve water quality and make coral reefs more resilient to stressors. Highlights: Mixing plots, isotopes, and sensors assessed nutrient patterns on resorts' coral reefs. Nutrients decreased from fresh groundwaters to offshore waters in resorts' watersheds. Nutrients mixed conservatively and non-conservatively between fresh and ocean waters. Groundwater, ocean, and fertilizer were dominate nutrient sources to coral reefs. Submarine groundwater discharge delivered nutrients to reefs in pulses of min to days.